Dogsred. 05 - Noda, Satoru (Viz signature., 2025)
Rou once chased figure-skating glory. Now he chases redemption in the ice hockey rink! Rou and the other Oinokami first-year students have made the cut and survived their first day on the team, but their training has only just begun. Despite the heat of summer, Oinokami forges ahead, practicing in indoor ice rinks. The former team captain, Higuchi, is back to town, but guilt over the team's loss has taken him down a dark path. Will the new team members follow him? Then it's time for the rookies to play in their first real game, against the decidedly delinquent players of Sekka High.